2017
DOI: 10.1017/s0033291717000319
|View full text |Cite
|
Sign up to set email alerts
|

Baseline demographics, clinical features and predictors of conversion among 200 individuals in a longitudinal prospective psychosis-risk cohort

Abstract: Background DSM-5 proposes an Attenuated Psychosis Syndrome (APS) for further investigation, based upon the Attenuated Positive Symptom Syndrome (APSS) in the Structured Interview for Psychosis-Risk Syndromes (SIPS). SIPS Unusual Thought Content, Disorganized Communication and Total Disorganization scores predicted progression to psychosis in a 2015 NAPLS-2 Consortium report. We sought to independently replicate this in a large single-site high-risk cohort, and identify baseline demographic and clinical predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 69 publications
5
41
0
2
Order By: Relevance
“…subcomponents on transition to psychosis was novel, in that each subcomponent was individually scored and evaluated to understand the underlying factors which might drive the strong association between total P.1. and transition to psychosis reported in the literature (Addington et al, ; Brucato et al, ; Cannon et al, ; Carrión et al, ; Ruhrmann et al, ), and replicated herein. Most importantly, this scoring method allows for an examination of a large CHR cohort with attenuated FRS.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…subcomponents on transition to psychosis was novel, in that each subcomponent was individually scored and evaluated to understand the underlying factors which might drive the strong association between total P.1. and transition to psychosis reported in the literature (Addington et al, ; Brucato et al, ; Cannon et al, ; Carrión et al, ; Ruhrmann et al, ), and replicated herein. Most importantly, this scoring method allows for an examination of a large CHR cohort with attenuated FRS.…”
Section: Discussionsupporting
confidence: 83%
“…Importantly, recent empirical evidence from the large‐scale NAPLS‐2 study suggests that total score on P.1. of the SIPS is significantly predictive of transition to psychosis (Addington et al, ; Cannon et al, ), and has demonstrated external validity in other samples (Carrión et al, ; Ruhrmann et al, ), including our own (Brucato et al, ).…”
Section: Introductionmentioning
confidence: 64%
“…For example, in the Evaluation and Follow‐up of Adolescents and Young Adults in São Paulo (ASAS) Program in Brazil, researchers studied a cohort of 18 participants meeting criteria for UHR, out of an initial sample of 894 (Brietzke et al, ). In this respect, our data represent a similar contribution, with 27 UHR subjects, which is not yet comparable with other larger cohorts described in the literature, such as the Personal Assessment and Crisis Evaluation (PACE) clinic in Melbourne, Australia (n = 416; Mechelli et al, ), the European Prediction of Psychosis Study (EPOS, n = 233; von Reventlow et al, ), the Center of Prevention and Evaluation (COPE), located in New York City (n = 200; Brucato et al, ) and the NAPLS‐2 (n = 764; Addington et al, ). Therefore, we are working to expand our network of clinical collaborators in Chile and more broadly across South America.…”
Section: Discussionsupporting
confidence: 71%
“…While subthreshold positive symptoms including unusual thought content , suspiciousness , and disorganized thinking have been shown to predict conversion to psychosis, perceptual abnormalities as a category have only mixed evidence with regard to their predictive validity. Some studies have demonstrated that higher perceptual abnormality scores are associated with higher‐than‐average CHR risk , but the majority have failed to demonstrate that P4 score is a significant predictor of conversion . Overall, this pattern does suggest a reappraisal of the role of perceptual abnormalities as a gross category in identifying individuals at high risk.…”
Section: Discussionmentioning
confidence: 99%